Blood flow response to a postural challenge in older men and women - Castellano, Vanessa (BioMed Central, 2004)
BACKGROUND: The purpose of this study was to measure blood flow in the carotid and femoral arteries, heart rate and blood pressure in response to postural challenge in older adults. A second purpose was to determine if older men and women have different cardiovascular responses to a postural challenge such as tilt. METHODS: Thirty-seven healthy elderly men and women participated in this study (69–82 years old). All subjects had similar physical activity levels. Postural challenge was induced by a 60° tilt at the level of the waist. Continuous carotid blood flow and femoral blood flow was measured with Doppler ultrasound. RESULTS: Carotid blood flow was significantly reduced 17% in both men and women immediately after tilt (p < 0.001), and by 3.2% two minutes after tilt (p < 0.001). Femoral blood flow decreased 59.4% in men and 61% in women immediately after tilt (p < 0.001), and remained significantly decreased two minutes after tilt by 21% (p <0.001). Heart rate increased by 15% in men (p < 0.001), and 26% in women immediately after the tilt (p < 0.001). Heart rate returned to resting values within two minutes in both men and women. Response to tilt was not significantly related to self-report physical activity levels or to six-minute walk time. CONCLUSION: A postural challenge induced larger changes in the femoral artery compared to the carotid artery. There were no differences between men and women to a tilt table test except for differences in heart rate response. There was no difference in the blood flow responses to postural challenge with physical activity level or between healthy older men and women.